2018
DOI: 10.3390/rs10091448
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of C-Band Quad-Polarization Synthetic Aperture Radar Wind Retrieval Models

Abstract: This work discusses the accuracy of C-2PO (C-band cross-polarized ocean backscatter) and CMOD4 (C-band model) geophysical model functions (GMF) for sea surface wind speed retrieval from satellite-born Synthetic Aperture Radar (SAR) images over in the Northwest Pacific off the coast of China. In situ observations are used for comparison of the retrieved wind speed using two established wind retrieval models: C-2PO model and CMOD4 GMF. Using 439 samples from 92 RADARSAT-2 fine quad-polarization SAR images and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…However, the high-spatial-resolution data obtained from the SAR satellite have good accuracy and results in offshore wind analysis (Yang et al, 2011). In recent years, various Geophysical Model Functions (GMFs), particularly the socalled C models (CMOD), tailored to assess wind parameters from SAR satellites have been successfully designed and developed, such as CMOD4 (Fang et al, 2018), CMOD-IFR2 (Jagdish et al, 2018), CMOD5 (Hersbach et al, 2005), CMOD5.n (Soisuvarn et al, 2013, CMOD7 (Stoffelen et al, 2017), and recently a new CMOD model was designed from RADARSAT-2 and S-1 satellite, the so-called C-SARMOD1, and C-SARMOD2 model (Radkani and Zakeri, 2020) for coastal wind speed retrievals (Lu et al, 2018). It should be noted that different types of C-band GMF models have the ability to measure wind speed using data obtained from the different S-1 satellites polarization with a 180 °ambiguous of the wind direction (Diaz et al, 2013).…”
Section: Wind Potential Assessmentmentioning
confidence: 99%
“…However, the high-spatial-resolution data obtained from the SAR satellite have good accuracy and results in offshore wind analysis (Yang et al, 2011). In recent years, various Geophysical Model Functions (GMFs), particularly the socalled C models (CMOD), tailored to assess wind parameters from SAR satellites have been successfully designed and developed, such as CMOD4 (Fang et al, 2018), CMOD-IFR2 (Jagdish et al, 2018), CMOD5 (Hersbach et al, 2005), CMOD5.n (Soisuvarn et al, 2013, CMOD7 (Stoffelen et al, 2017), and recently a new CMOD model was designed from RADARSAT-2 and S-1 satellite, the so-called C-SARMOD1, and C-SARMOD2 model (Radkani and Zakeri, 2020) for coastal wind speed retrievals (Lu et al, 2018). It should be noted that different types of C-band GMF models have the ability to measure wind speed using data obtained from the different S-1 satellites polarization with a 180 °ambiguous of the wind direction (Diaz et al, 2013).…”
Section: Wind Potential Assessmentmentioning
confidence: 99%
“…A hybrid wind retrieval model is proposed by using two models: C-2PO (C-band cross-polarized ocean backscatter) and CMOD4 (C-band model) [7]. Sets of SAR images over the Northwest Pacific off the coast of China are used to establish a wind speed threshold (9.4 m/s).…”
Section: Overview Of Contributionsmentioning
confidence: 99%
“…In this context, numerous studies already demonstrated the potential to use satellite synthetic aperture radar (SAR) measurements to provide TC surface wind field at very high resolution (Katsaros et al 2000;Li et al 2013). This unique mapping capability, further supported by highly sensitive cross-polarization measurements to increasing winds, has often been highlighted with respect to SFMR (Zhang and Perrie 2012;Horstmann et al 2015;Mouche et al 2019), buoys (Vachon and Wolfe 2011;Zhang et al 2012), L-band passive remote sensing measurements (Mouche et al 2017;Zhao et al 2018), and global models (Fang et al 2018). Still, most of these TC studies were not based on a large number of cases, especially those cases reaching winds higher than 40 m s 21 .…”
Section: Introductionmentioning
confidence: 99%